An appraisal of the Laguna approach to community education - Avenido, Emilio A. 1904- (University of the Philippines], 1957)
This appraisal is a technique for community education and community improvement that was conceived and developed by schoolmen -- teachers, supervisors, and school administrators in the Division of Laguna during the latter part of the school year 1953-1954 and applied in all school communities since then. Its essential features, roadblocks or difficulties encountered in its application and improvement of the approach were determined in this study.